Methods and Results of the Study of the Phenomenon of Soviet Nostalgia in the Russian Media Space - Ivan V. Suslov; Sofya V. Tikhonova (Гуманитарный вектор)
The article is devoted to the phenomenon of digitalization of Soviet nostalgia. Special attention is paid to the nature of modern media discussions about the Soviet past, in which anti-communist sentiments are intertwined with nostalgia for the late Soviet period. The relevance of the study is connected with the increasing infl uence of a wide public audience in the era of digitalization on historical memory, previously formed mainly by professional historians and ideologists. The USSR is seen as a “place of memory” (according to Pierre Nora), which has a special symbolic signifi cance at the modern stage of development. The authors emphasize the changing balance between communicative and cultural memory in the era of digital technologies, as well as the need to develop new methods of analysis to work with huge amounts of data. The review of current studies of Soviet nostalgia in the media space allows us to identify the main vectors of development of Russian digital humanities, as well as analyze the reasons for the continued interest in nostalgic discussions in online communities, social networks and other media platforms. We make a conclusion that in modern scientifi c discourse there are two approaches to the study of the image of the USSR in the mass consciousness: fi rst, the analysis of the content of media content about “the Soviet” (very diverse in quality and form), and second, the study of user/viewer reaction (reception). There is an indication of tendencies in the Russian media space to depoliticize the discussion of the Soviet period. However, nostalgic debates continue to mark the boundaries of the confrontation between liberals-anti-Soviets, Soviet patriots and patriots-patriots, indicating the presence of several ideological splits in Russian society. Social networks become a platform for the formation of alter and counter narratives, contributing to the maintenance of pluralism of opinions and knowledge about the past. The study reveals three components of nostalgic discussions: comparison of the past and the present, ideological opposition, (and the least politicized) admiration for Soviet aesthetics and everyday life.